Design, Development, Implementation, and Evaluation of a Mobile Application for Academic Library Services: A Study in a Developing Country. - Saeidnia, Hamid Reza; Kozak, Marcin; Lund, Brady; Mannuru, Nishith Reddy; Keshavarz, Hamid; Elango, Bakthavachalam; Babajani, Afshin; Ghorbi, Ali (Information Technology & Libraries, 2023)
Universities and scientific educational institutions today need targeted information services to ensure that their user communities have the information they need. This study aims to design, develop, implement, and evaluate a mobile application for academic library services at Tarbiat Modares University (Tehran, Iran). A four-stage process was utilized to accomplish this aim. In the first phase, relevant literature was reviewed to obtain appropriate data requirements for the app. A questionnaire was designed and administered to survey expert librarians on the most suitable data requirements. The second phase involved the design of the user interface and user experience with the assistance of experts, followed by the evaluation of the experience. The third phase involved the development of the app in the Android Studio environment using the Java programming language, based on the requirements identified in the first and second phases. The app was then made available to the user community. Finally, the app was evaluated in the fourth phase using a questionnaire tool. The researchers found this approach to application development to be both economical and effective in the context of a developing country.